Person-organization fit and turnover intention: Conceptualizing the moderating role of social exchange ideology - Memon, M.A. (American Scientific Publishers, 2015)
Although person-organization fit has been regarded as one of the strongest predictors of employee turnover, the aggregated results of several meta-analytic and quantitative review studies indicate a weak statistical relationship between person-organization fit and turnover intention. The key objective of this paper is to conceptualize the moderating role of social exchange ideology in enhancing the relationship between person-organization fit and the individualsâ intention to leave their job. Our conceptualization of moderation is based on the argument that the compatibility, or fit, of attributes between both parties (employee and organization) may be valued highly by employees with a stronger social exchange ideology. In turn, this might result in individuals who are more responsive and, consequently, less likely to resign from their job. The social exchange theory, Attraction- Selection-Retention framework, and past empirical evidence were taken into account to provide a theoretical support for the proposed framework. As the moderating role of social exchange ideology has been less articulated with regard to person-organization fit and turnover intention, the purpose of the present paper is to fill that research gap. Recommendations for future research are also proposed. Â© 2015 American Scientific Publishers. All rights reserved.